Comparative study of aquaculture industry in Africa a case study on trend of aquaculture industry in Nigeria and some coastal countries for a decade - Ibrahim, M.; Daud, H. M.; Kamarudin, M. S.; Abdelhadi, Y. M.; Karim, Murni (Researchjournali, 2015)
The only way Africa can sustain fisheries development is through Aquaculture for food production in the continent. The paper examined trend of aquaculture industry for a decade among some leading African countries and less privilege ones with emphasis on fisheries resources, challenges and development. Secondary data were collected from relevant literature as well as the Food and Agriculture Organization of the United Nations (FAO) data base. Descriptive statistics were employed in data analysis. Aquaculture industry is developed in Nigeria and Ghana when compares with other coastal nations of Africa. Disparity will still remain hence the industries is yet to make a significant contribution to national food and nutrition security of these African nations.